Back to the Future : The Khanate of Kalat and the Genesis of Baloch Nationalism, 1915-1955 - Axmann, Martin (Karachi Oxford University Press, 2016)
The study investigates the genesis of Baluch nationalism during the first half of the twentieth century, analyses the emergence of a Baluch national movement, and sets it into relation to the rise of an Indian and Muslim Indian (Pakistan) national movement in British India during that time. The study portrays the decline and disintegration of the Baluch khanate of Kalat during the last decades of British rule, analyses Kalat's lack of integration but increasing attachment to British Indian affairs, and summarises the colonial legacy of Baluchistan in respect of political, administrative and constitutional development. It investigates the emergence of a royalist movement around the figure of the khan of Kalat, and discusses his attempt to turn back time and revert to Baluchistan's pre-colonial status. It probes into the coincident rise of a Baluch nationalist movement, and analyses the political and cultural framework of an emerging Baluch national identity. It traces the political demands of Baluch nationalist pioneers, and looks for interrelations with the Baluch royalist and Indian Muslim nationalist movements. It ascertains the emergence of a Baluch national movement as the outcome of the historical and political circumstances during the British withdrawal from India, and portrays the evolution of Baluch national identity as a reaction to the territorial, political and cultural inclusion on side of the All India Muslim League and the Pakistan movement.
Include Bibliography and Index
Keywords: Nationalism -- Pakistan--Balochistān -- Asia--Kalat (Princely State)